أثر مبدأ حسن النية في إنهاء عقود المدة: دراسة تحليلية مقارنة - فتح الباب، محمد ربيع أنور (جامعة القاهرة - كلية الحقوق - فرع الخرطوم, 2022)
يعد مبدأ حسن النية من المبادئ الأخلاقية المستقرة والثابتة، التي يجب أن تسود جميع العلاقات التعاقدية، بدءا من مرحله التفاوض مرورا بمرحلتي: الإبرام والتنفيذ، وانتهاء بمرحلة إنهاء العقد، وقد تلقفته التشريعات المدنية في العديد من الدول من القانون الروماني. ويعني مبدأ حسن النية في مجال العقود، ضرورة أن يتحلى كل طرف من أطراف العلاقة التعاقدية بالصدق والأمانة والإخلاص، وألا يتناقض في تصرفاته أو أفعاله، بما ينبئ عن سوء نية، وبحيث يكون مسؤولا عن تعويض الأضرار التي تصيب الطرف الآخر جراء التصرف بسوء نية. غير أن المشرع المصري يقصر مبدأ حسن النية في العقود في مرحلة تنفيذها فقط، كما جرى النص على ذلك في المادة (١٤٨) من القانون المدني، بعكس المشرع الفرنسي الذي يطلق هذا المبدأ بصورة ملزمة على مراحل: التفاوض، والإبرام، والتنفيذ، كما جرى النص على ذلك في المادة (١١٠٤) من القانون المدني، وفي تشريعات فرنسية أخرى. وعلى الرغم من اهتمام العديد من التشريعات بالنص على مبدأ حسن النية، إلا أنها لم تنص صراحة على هذا المبدأ في مرحلة إنهاء عقود المدة، وتحديدا عند إعمال ما تتضمنه تلك العقود من جزاءات اتفاقية كالشرط الفاسخ والتعويض الاتفاقي أو كما يطلق عليه "الشرط الجزائي"، وكذا تلك التي تقوم على العمل، كعقد العمل وعقد الوكالة؛ إذ يظهر مبدأ حسن النية بجلاء في مرحلة إنهاء تلك العقود، بحيث يتعين على كل طرف أن ينهي العقد -متى أراد ذلك -بحسن نية، إلى جانب التقيد بالضوابط القانونية المنصوص عليها في هذا الشأن. فمبدأ حسن النية كما هو مطلوب بإلزام في مراحل التفاوض على العقد وإبرامه وتنفيذه؛ فهو كذلك مطلوب بذات القدر من الإلزام والأهمية في مرحلة إنهاء عقود المدة؛ فكما أن الدخول في علاقات عقدية يستلزم حسن النية في الطرفين؛ فإن التحلل منها يستلزم كذلك من الطرفين التحلي بذات الأمر. وتبحث هذه الدراسة أثر مبدأ حسن النية في مرحلة إنهاء عقود المدة في القانون المدني المصري، مع المقارنة بالقانون المدني الفرنسي وقوانين أخرى، كالقانون المدني لمقاطعة "كيبيك" الكندية. The principle of good faith is a stable and established moral principle, which must prevail in all contractual relationships, from negotiation through to conclusion and implementation and ending with the stage of contract termination. Civil Codes in many countries have taken it from Roman law. The principle of good faith in the field of contracts means that each of the parties to the contractual relationship must be honest, trustworthy and ethical, and not contradict in his actions, and so that he is responsible for compensating the damages caused to the other party as a result of acting in bad faith. However, the Egyptian legislator limits the principle of good faith in contracts to the stage of contract implementation only, as was stipulated in Article (148) of the Civil Code, in contrast to the French legislator who generalizes this principle with a binding manner to stages: negotiation, conclusion, and implementation, as stipulated in Article (1104) of the Civil Code, and in other French Codes. Despite the interest of many legislators to stipulate the principle of good faith, they did not specifically provide for this principle at the stage of termination of fixed-term contracts, specifically those contracts that include agreement sanctions, such as resolutory clause and agreement compensation or as it is called the "penalty clause", as well as those which are based on work, such as the employment contract and the agency contract; The principle of good faith appears clearly at this stage, so that each party must terminate the contract- whenever it wants- in good faith, in addition to adhering to the legal controls stipulated in this regard. The principle of good faith, as required with binding in the stages of negotiation, conclusion and implementation of the contract; It is also required with equally important at the stage of termination of fixed-term contracts; Just as entering into contractual relations requires goodwill on both sides; The dissolution of them also requires both parties to show this. This paper examines the impact of the principle of good faith in the phase of termination of fixed-term contracts in the Egyptian Civil Code, compared to the French Civil Code, and other laws, such as: Civil Code of Quebec.
Keywords: العقود -- مدة العقود -- العلاقات التعاقدية -- المبادئ القانونية -- مبدأ حسن النية -- القانون المدني المصري -- القانون المدني الفرنسي